Design parameters for voltage-controllable directed assembly of single nanoparticles. - Porter, B; Abelmann, L; Bhaskaran, H (2013)
Techniques to reliably pick-and-place single nanoparticles into functional assemblies are required to incorporate exotic nanoparticles into standard electronic circuits. In this paper we explore the use of electric fields to drive and direct the assembly process, which has the advantage of being able to control the nano-assembly process at the single nanoparticle level. To achieve this, we design an electrostatic gating system, thus enabling a voltage-controllable nanoparticle picking technique. Simulating this system with the nonlinear Poisson-Boltzmann equation, we can successfully characterize the parameters required for single particle placement, the key being single particle selectivity, in effect designing a system that can achieve this controllably. We then present the optimum design parameters required for successful single nanoparticle placement at ambient temperature, an important requirement for nanomanufacturing processes.